Dr. Lakhdar Belhaouari — Deep Plane Facelift — Toulouse - Belhaouari, Lakhdar (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Lakhdar Belhaouari, practicing in Toulouse, France. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003214; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; france; toulouse